Active break and work climate in academic and administrative areas of Universidad Peruana Unión, 2018 - Ibañez Asto, Agata Samantha (2019)
Objective: To determine the relationship between the level of practice of Active Pause and Labor Climate in academic and administrative areas of the Universidad Peruana Unión. Methodology: The study design was non-probabilistic quantitative, descriptive type, cross-sectional correlation; The active pause survey and the work climate were applied to 200 people who previously participated in the “Active Pause at Universidad Peruana Unión” program “Active Pause at the Universidad Peruana Unión”. Results: The 59.5% sometimes practice the active pause and 86% maintain a good working climate, in the statistical analysis of correlation Tau-b of Kendall had a p-value score = 0.307, which indicates that there is no relationship between active pause and work climate, as well as the dimensions of Organization p-value = 0.178, Communication p-value = 0.525, Working conditions p-value = 0.376 which also have no significant relationship, unlike the dimensions of Social interaction p-value = 0.038 and that of Identity and belonging p-value = 0.025, which have a significant relationship with the active pause variable. Conclusion: It was not found a relationship in both variables, nor in three dimensions (organization, communication and working conditions), only in two of them (social interaction and identity and belonging). statistically significant correlation between CVR and lifestyle (p=0.234),nevertheless it was found a correlation between CVR and eating habits (p=0.012).